Association between physical education, school-based physical activity, and academic performance: a systematic review (Asociación entre la educación física, la actividad física en la escuela, y el rendimiento académico: una revisión sistemática) - Marques, Adilson; Gómez, Francisco; Martins, João; Catunda, Ricardo; Sarmento, Hugo (Retos, 2017)
Background: The time allocation for physical education school-based physical activity is often replaced with other classes in an effort to increase children’s academic performance. However, a growing body of literature suggests that physical activity either had no effect on academic performance or that it enhanced it. Objective: The purpose of this report is to perform a systematic review of the evidence on the associations between physical education and school-based physical activity, and academic performance. Design: Systematic review. Methods: Studies were identified through research of the PubMed, Sportdiscus, and Web of Science databases from 2000 through 2016. The titles and abstracts were screened for eligibility, the methodological quality of the studies was rated, and data was extracted. The main exposure was physical education or school-based physical activity. For the main outcome, studies had to report at least one academic performance measure. Results: A total of 12 articles met the inclusion criteria; four of them were cross-sectional, two longitudinal, two quasi-experimental and four interventional studies. Seven articles found a positive association between physical education or school-based physical activity and academic performance, four found no association and in one there was a positive association for 3rd grade students and a negative association for 2nd grade students. Conclusion: In general, results of the review support that physical education or school-based physical activity is positively associated with academic performance in children.Resumen. Introducción: La asignación de tiempo para la actividad física o la educación física en escuelas a menudo se sustituye con otras clases, en un esfuerzo para incrementar el rendimiento académico de los niños. Sin embargo, un número creciente de estudios sugieren que la actividad física o no tiene algún efecto sobre la mejora del rendimiento académico. Objetivo: El objetivo de este manuscrito es realizar una revisión sistemática de la evidencia sobre la asociación entre la educación física y la actividad física en la escuela, y el rendimiento académico. Diseño: Revisión sistemática. Métodos: Se identificaron estudios a partir de búsquedas en las bases de datos PubMed, Sportdiscus y Web of Science de 2000 a 2016. Se proyectaron los títulos y los resúmenes de elegibilidad, se calificó la calidad metodológica de los estudios y se extrajeron los datos. Las principales exposiciones fueron la educación física o la actividad física en la escuela durante el horario escolar. Para el resultado principal, los estudios debían informar al menos una medida de rendimiento académico. Resultados: Un total de 12 artículos cumplieron los criterios de inclusión, cuatro de ellos eran de la sección transversal, dos longitudinales, dos cuasi-experimental y cuatro estudios de intervención. Siete artículos encontraron una asociación positiva entre la educación física o la actividad física en las escuelas y el rendimiento académico, en cuatro no se encontró ninguna asociación y en uno se encontró una asociación positiva para los estudiantes de 3er grado y una asociación negativa para los estudiantes de 2do grado. Conclusión: En general, los resultados de la revisión apoyan que la educación física o la actividad física en la escuela se asocia positivamente con el rendimiento académico en los niños.